2009
DOI: 10.1111/j.1574-6968.2009.01588.x
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific recombination of T2 phage using IP008 long tail fiber genes provides a targeted method for expanding host range while retaining lytic activity

Abstract: The application of bacteriophages (phages) in therapy urgently requires the production of wide-host-range recombinant phages that possess strong lytic activity. The wide-host-range IP008 phage was classified by transmission electron microscopy analysis as an A2 morphotype member of the Myoviridae family of the order Caudovirales. IP008 showed a high homology (99.4% similarity in the amino acid alignment of the major capsid protein Gp 23) with KEP10, another wide-host-range phage. The long tail fiber genes (gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 19 publications
0
75
0
Order By: Relevance
“…While phage-induced lysis can be combined with IMS to detect E. coli (62) and Salmonella (63) based on phage-encoded biomarker amplification, lysis may also be problematic if downstream identification requires the recovery of viable cells-an issue not associated with LTFs and other phage-encoded proteins with no inherent lytic activity. Moreover, single proteins or even protein complexes (such as gp37-gp38) are still much smaller than whole phage particles, less complicated to produce as a single entity, and easier to modify in order to alter or optimize their recognition properties (47,64,65). This was elegantly demonstrated by Singh et al, who observed a 6-fold increase in Salmonella immobilization in an SPR-based biosensor by removing the inherent endorhamnosidase activity of the phage P22 tail spike probe (39).…”
Section: Discussionmentioning
confidence: 67%
“…While phage-induced lysis can be combined with IMS to detect E. coli (62) and Salmonella (63) based on phage-encoded biomarker amplification, lysis may also be problematic if downstream identification requires the recovery of viable cells-an issue not associated with LTFs and other phage-encoded proteins with no inherent lytic activity. Moreover, single proteins or even protein complexes (such as gp37-gp38) are still much smaller than whole phage particles, less complicated to produce as a single entity, and easier to modify in order to alter or optimize their recognition properties (47,64,65). This was elegantly demonstrated by Singh et al, who observed a 6-fold increase in Salmonella immobilization in an SPR-based biosensor by removing the inherent endorhamnosidase activity of the phage P22 tail spike probe (39).…”
Section: Discussionmentioning
confidence: 67%
“…However, comparative genomic analysis showed that even though they share most functional genes for phage reconstruction, host specificity-related genes are quite different, which may affect host infection. A recent phage-engineering study involving tail fiber protein replacement showed changes in host specificity, substantiating this hypothesis (43). It is intriguing that the tail fiber protein in phage SFP10 may target the LPS receptor of host E. coli O157:H7, similar to phage phiV10, but the tail spike protein in the same gene cluster may target the LPS receptor of host S. enterica, similar to phage Det7, suggesting how phage SFP10 can infect both bacteria (Table 3).…”
Section: Discussionmentioning
confidence: 74%
“…Some of these bottlenecks are already being addressed by the introduction of molecular biology techniques that enable the genetic engineering of phage genomes. For example, phages have been genetically engineered to enhance their performance against biofilms (85), to improve antibiotic activity (86,87), and to expand their host ranges (88)(89)(90)(91). The use of well-defined and purified phage preparations is also crucial for therapeutic applications and for regulatory approval (83,92).…”
Section: Current Challenges Faced By Phage Therapymentioning
confidence: 99%